A new species of Ptenothrix Börner, 1906 (Collembola, Symphypleona, Dicyrtomidae) from South Korea - Jo, Seon Hwa; Park, Kyung-Hwa (Zootaxa, 2023)
A new species of Collembola, Ptenothrix koreanensis sp. nov., is described and illustrated based on specimens from South Korea. It was found in a coniferous forest dominated by the Korean pine Pinus koraiensis Siebold & Zuccarini. Ptenothrix koreanensis sp. nov. is characterized by a peculiar color pattern in which most of its median dorsal side of the large abdomen is plain milky white. This new species also has the formula of 1, 1, 2, 2, 1, 3 of median spiny chaetae on the clypeal area of the head, and the formula of 6, 5, 5, 4 of prelabral and labral chaetae. These characteristics make it easy to distinguish the new species from other two possibly related species, P. ciliophora Yosii & Lee and P. saxatilis Yosii & Lee. Apart from these characteristics, the new species can also be separated from another possibly related species, P. higashihirajii Yosii, by the morphology of ps1 and pi2 chaetae on the small abdomen of the female. An identification key for the East Asian species of Ptenothrix is also provided.